The potential of energy refurbishment through the integration of daylight harvesting for office buildings in Universiti Sains Islam Malaysia - Arabi F.; Husini E.M.; Ismail W.N.W.; Ja'Afar N.H. (American Scientific Publishers, 2024)
The Universiti Sains Islam Malaysia (USIM) has outline steps to achieve sustainable development and environmentally friendly starting year 2014 which stipulated that all faculties and offices building to be incorporated with sustainable design features and occupants awareness toward energy efficiency building. However, the questions on the existing building design still ponders and requires a research on whether the implementation of the design has met the criteria to achieve energy efficiency building and does the adoption of passive design strategies, such as building orientation, windows size and control window system has taken all the consideration on the penetration of daylight into the building without compromising to the occupant visual comfort. A Qualitative survey with 60 respondents from five different departments has been conducted on the occupants perception toward visual comfort due to daylight quantity penetrated from window compare to the data analysis done from IES-Ve on daylighting quantity and quality of the selected departments. Finding from the survey shown that 61.2% of the respondents agreed that there is a visual discomfort from the windows of the office and 52.2% respondent agreed that tinted window reduce the penetration of daylight. Solutions from the literature review on integration of passive and active design strategies are proposed in the retrofitting of the building to harvest the natural lighting and increase the daylight quantity in the building. The research will be useful as basic recommendation on the retrofitting process to harvest the natural lighting and increase the energy efficiency in retrofitting the faculty and office building in USIM. 2017 American Scientific Publishers All rights reserved.